Diagnostic performance of D-dimer in predicting venous thromboembolism and acute aortic dissection. Issue 5 (18th March 2020) - Koch, Vitali; Biener, Moritz; Müller-Hennessen, Matthias; Vafaie, Mershad; Staudacher, Ingo; Katus, Hugo A; Giannitsis, Evangelos
Abstract: Background: D-dimer is elevated in a variety of conditions. The purpose of this study was to assess the positive predictive value of D-dimer to rule in patients with confirmed pulmonary embolism, deep vein thrombosis, acute aortic dissection or thrombosis of the upper extremity in comparison to patients with elevated D-dimer for other reasons. Methods and results: We studied 1334 patients presenting to the emergency department with pulmonary embolism ( n =193), deep vein thrombosis ( n =73), acute aortic dissection ( n =22), thrombosis of the upper extremity ( n =8) and 1038 controls. The positive predictive value was increased with higher D-dimer concentrations improving the ability to identify diseases with high thrombus burden. Patients with venous thromboembolism, acute aortic dissection and thrombosis of the upper extremity showed a maximum positive predictive value of 85.2% at a D-dimer level of 7.8 mg/L (95% confidence interval (CI) 78.1 to 90.4). The maximum positive predictive value was lower in cancer patients with venous thromboembolism, acute aortic dissection and thrombosis of the upper extremity, reaching 68.9% at a D-dimer level of 7.5 mg/L (95% CI 57.4 to 78.4). The positive likelihood ratio was very consistent with the positive predictive value. Using a cut-off level of 0.5 mg/L, D-dimer showed a high sensitivity of at least 93%, but a very low specificity of nearly 0%. Conversely, an optimised cut-off value of 4.6 mg/L increased specificity to 95% for the detection of life-threatening venous thromboembolism, acute aortic dissection or thrombosis of the upper extremity at the costs of moderate sensitivities (58% for pulmonary embolism, 41% for deep vein thrombosis, 65% for pulmonary embolism with co-existent deep vein thrombosis, 50% for acute aortic dissection and 13% for thrombosis of the upper extremity). Using the same cut-off in cancer patients, higher values were observed for sensitivity at a specificity level of more than 95%. The area under the curve for the discrimination of venous thromboembolism/acute aortic dissection/thrombosis of the upper extremity from controls was significantly higher in cancer versus non-cancer patients (area under the curve 0.905 in cancer patients, 95% CI 0.89 to 0.92, vs. area under the curve 0.857 in non-cancer patients, 95% CI 0.84 to 0.88; P =0.0349). Conclusion: D-dimers are useful not only to rule out but also to rule in venous thromboembolism and acute aortic dissection with an at least moderate discriminatory ability, both in patients with and without cancer.